2007
DOI: 10.1016/j.cell.2007.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Patterning Signals: Wnt/GSK3 Regulates the Duration of the BMP/Smad1 Signal

Abstract: BMP receptors determine the intensity of BMP signals via Smad1 C-terminal phosphorylations. Here we show that a finely controlled cell biological pathway terminates this activity. The duration of the activated pSmad1(Cter) signal was regulated by sequential Smad1 linker region phosphorylations at conserved MAPK and GSK3 sites required for its polyubiquitinylation and transport to the centrosome. Proteasomal degradation of activated Smad1 and total polyubiquitinated proteins took place in the centrosome. Inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
555
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 498 publications
(575 citation statements)
references
References 39 publications
20
555
0
Order By: Relevance
“…While the BMP signaling domain is dorsally expanded in wnt8;chordin double morphants, lower levels of p-Smad1/5 staining at 80% epiboly stand in contrast to consistently elevated p-Smad1/5 staining in chordin morphants. Decreased pSmad1/5 staining in the double morphant is consistent with a recently proposed role for Wnt signaling in stabilization of activated Smads (Fuentealba et al, 2007), but it also correlates with the absence of bmp2b expression in the embryonic margin. However, bmp2b absence from the margin may not be relevant as bmp4 and bmp7 expression recovers in the double morphant.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…While the BMP signaling domain is dorsally expanded in wnt8;chordin double morphants, lower levels of p-Smad1/5 staining at 80% epiboly stand in contrast to consistently elevated p-Smad1/5 staining in chordin morphants. Decreased pSmad1/5 staining in the double morphant is consistent with a recently proposed role for Wnt signaling in stabilization of activated Smads (Fuentealba et al, 2007), but it also correlates with the absence of bmp2b expression in the embryonic margin. However, bmp2b absence from the margin may not be relevant as bmp4 and bmp7 expression recovers in the double morphant.…”
Section: Discussionsupporting
confidence: 86%
“…However, one difference observed between chordin and wnt8;chordin morphants is that the staining intensity is slightly lower in the double knockdown (compare Fig. 3 C and D, K and L), perhaps reflecting a role for Wnt signaling in stabilizing phosphorylated Smad (Fuentealba et al, 2007). From these results, we deduce that reducing Chordin expression results in elevated BMP signaling in a wnt8 loss-of-function background.…”
Section: Bmp Signaling Is Rescued In Wnt8;chordin Double Loss-offunctmentioning
confidence: 74%
See 1 more Smart Citation
“…The latter notion is further confirmed by localization of the proteasome subunit S20a5 and polyubiquitin to the centrosomes in this cell line. 72 Subsequent experiments revealed that phospho-Smad1 localized asymmetrically to mitotic centrosomes in human embryonic stem cells (hESCs). Phospho-Smad1 also colocalized with centrosomal microtubules.…”
Section: Centrosome-associated Degradation Of Cell Fate Determinantsmentioning
confidence: 99%
“…BMP-induced Smurf1 can, as in the steady-state condition, ubiquitinate and degrade Smad1 and Smad5 [40]. In the case of Smad1, it is known that after phosphorylation at the C-terminal motif by the BMP type I receptors, sequential phosphorylations follow in the linker region of Smad1 by MAPK and GSK3b [47,48]. These linker phosphorylations lead to poly-ubiquitination and degradation of activated Smad1 via Smurf1 (Figure 2).…”
Section: Regulation Of R-smad Stabilitymentioning
confidence: 99%